Hepatoprotective Effect of aqueous Rosemary extract on amoxicillin induced hepatocytotoxicity in Syrian Hamster (Latakia University Journal -Biological Sciences Series, 2018)
The present study aimed to evaluate the hepatoprotective proprieties of aqueous rosemary extract against amoxicillin induced cytotoxicity in liver tissues of Syrian hamster. Thirty-six mal hamsters divided into six groups of six hamsters each were used. Group 1 (control) was received normal food and water for a period of 6 weeks, group 2 received orally a dose of rosemary extract (220 mg/b.w) daily for sex weeks also. Groups 3 and 4 were orally received an amoxicillin dose at 40 and 50 mg/kg body weight respectively three times/week,  while Groups 5 and 6 were received Rosemary extract (220 mg/kg b.w) daily for one week then an amoxicillin dose at 40 and 50 mg/kg body weight in combination with aqueous rosemary extract (220 mg/Kg b.w) for five weeks. Biochemical study showed a significant increase in the levels of ALT (p